Assassin's creed [videorecording (DVD)] - Fassbender, Michael, 1977-; Cotillard, Marion, 1975-; Irons, Jeremy, 1948- (Twentieth Century Fox Home Entertainment, 2017)
Through a revolutionary technology that unlocks his genetic memories, Callum Lynch experiences the adventures of his ancestor, Aguilar, in 15th Century Spain. Callum discovers he is descended from a mysterious secret society, the Assassins, and amasses incredible knowledge and skills to take on the oppressive and powerful Templar organization in the present day.